Relative contributions of statin intensity, achieved low-density lipoprotein cholesterol level, and statin therapy duration to cardiovascular risk reduction in patients with type 2 diabetes: population based cohort study - Ji Yoon Kim; Jimi Choi; Sin Gon Kim; Nam Hoon Kim (Cardiovascular Diabetology, 2022)
Abstract Background Current guidelines recommend life-long use of statin for patients with type 2 diabetes (T2D), however, a number of patients discontinue statin therapy in clinical practice. We aimed to estimate the optimal statin therapy including statin therapy duration, statin intensity, and low-density lipoprotein cholesterol (LDL-C) level among patients with T2D in a real-world setting. Methods From Korean National Health Insurance Service Cohort (2007–2015), 8937 patients with T2D (≥ 40 years of age) who received statin therapy for at least 90 days were included. Risk of major adverse cardiovascular event (MACE) including ischemic heart disease, ischemic stroke, and cardiovascular death was estimated according to statin intensity, achieved serum LDL-C level, and statin therapy duration, respectively. The relative contributions of these factors to MACE risk were quantified by calculating the proportion of log-likelihood explained by each factor. Results The hazard ratio (HR) of MACE was lower in patients receiving moderate- or high-intensity statins than in those receiving low-intensity statins (HR, 0.72; p = 0.027). Among patients who received moderate- or high-intensity statins, lower achieved LDL-C level was associated with lower cardiovascular risk. Notably, the longer the patients received statins, the lower was the risk of MACE; the HR of MACE was significantly reduced after at least 18 months (adjusted HR, 0.70; p = 0.009) as a reference to 3–6 months of therapy. The proportion of explainable log-likelihood for MACE was greatest for statin duration (2.55), followed by achieved LDL-C level (2.18), and statin intensity (0.95). Conclusions Statin therapy duration is as important as or more crucial than statin intensity or achieved LDL-C level for the reduction of cardiovascular risk in T2D patients. The concept of “longer is better” regarding statin therapy should be considered in clinical practice.